2007
DOI: 10.1590/s1413-86702007000600010
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant urinary tract isolates of escherichia coli from Ribeirão Preto, São Paulo, Brazil

Abstract: Multiple resistances to antimicrobial drugs arising in Escherichia coli isolates may complicate therapeutic management of urinary tract infection (UTI) by this organism. In order to assess the multidrug resistance (MDR) among urinary E. coli isolates, we have tested 11 antimicrobial drugs against 67 isolates from outpatients attended in a tertiary-care teaching hospital and of 78 isolates from a municipal health unit, respectively in Ribeirão Preto, State of São Paulo, Brazil. Seventy-six percent and 22% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…However, in our study the situation becomes escalated to 92.9%. Besides, with reference to previous reports, E. coli isolates were found to be highly resistant to commonly prescribed antibiotics, such as AMP, cotrimoxazole, C, GEN, and CTZ [8,[20][21][22][23], which shows an agreement with the results reported in this study. Therefore, these antibiotics should not be recommended as a first line to treat UTIs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in our study the situation becomes escalated to 92.9%. Besides, with reference to previous reports, E. coli isolates were found to be highly resistant to commonly prescribed antibiotics, such as AMP, cotrimoxazole, C, GEN, and CTZ [8,[20][21][22][23], which shows an agreement with the results reported in this study. Therefore, these antibiotics should not be recommended as a first line to treat UTIs.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, it showed that high prevalence of MDR E. coli isolates identified from patients with UTI was 92.9% (95% confidence interval: 87.3%-97.7%). The rate of MDR E. coli demonstrated in this study was much higher than findings from developed countries [8][9][10], but comparable to published data from low income countries [4,5,11,12]. However, few reports from developing countries documented lower prevalence of MDR E. coli as compared to this study [13][14][15][16].…”
Section: Discussionsupporting
confidence: 80%
“…However, they can be used in complicated UTI as they decrease hospitalization time [18] . In longitudinal studies, prevalence of ciprofloxacin resistance increased over time [3,19] , reaching almost 20% in countries such as Spain and Portugal [3] . The prevalence of ciprofloxacin resistance seems to be higher in Latin America [3,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is necessary to have updated knowledge of causal bacteria and their susceptibility patterns for proper selection and use of antibiotics as well as for an appropriate prescribing guideline. [4] It is hoped that the information gained from this study would help in the treatment of cases of UTI in our area. Antibiotic susceptibility pattern differences seen between countries and also different medical regions within every country.…”
Section: Introductionmentioning
confidence: 92%